Firework Launcher Application System In Dangdut Orches Show Using Arduino Based On Android: Sistem Aplikasi Pemantik Kembang Api (Firework Launcher Application System) Pada Pertunjukan Orkes Dangdut Menggunakan Arduino Berbasis Android - Bagus Permadi Putra; Suprianto (Academia Open, 2021)
One of the current trending phenomena is performances or celebratory activities that are enlivened by lighting fireworks. The ignition of fireworks is usually done using a remote firework lighter (firing system) or even manually if the lighter is having problems/not working. It is still possible for operator accidents to be burned by fireworks. In addition to security issues, remote fireworks lighters are quite expensive. Therefore, to avoid security problems and the relatively high price, it is necessary to create or build a firework launcher system that is safe and inexpensive. The purpose of this study is to create a firework launcher application system for dangdut orchestra performances using an Android-based Arduino. In this study, an application has been produced that can make it easier for operators of fireworks lighters in dangdut orchestras to light fireworks more safely and cheaply. This application has been running smoothly and without problems. The benefit of this research is that the results of this application design can be used as a reference for other related research in the future.